2015
DOI: 10.1111/jre.12302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycated albumin and cranberry components on interleukin‐6 and matrix metalloproteinase‐3 production by human gingival fibroblasts

Abstract: G-HSA ± LPS may have differential effects on IL-6 and MMP-3 production by human gingival fibroblasts, but both are inhibited by NDM. The study suggests that cranberry phenols may be useful in regulating the host response and perhaps treating periodontitis in patients with poorly controlled diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
3
14
0
Order By: Relevance
“…However, HSA did not significantly stimulate IL‐6 or IL‐8 production (except at the highest concentrations tested and at the longest exposure time). This is consistent with our previous work, and others have shown that G‐HSA stimulated IL‐8 and/or IL‐6 production in human chondrocytes and fibroblast‐like synovial cells . Glycated HSA and/or glycated bovine serum albumin (BSA) also stimulated IL‐6 and IL‐8 produced by gingival fibroblasts and monocyte/macrophages .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, HSA did not significantly stimulate IL‐6 or IL‐8 production (except at the highest concentrations tested and at the longest exposure time). This is consistent with our previous work, and others have shown that G‐HSA stimulated IL‐8 and/or IL‐6 production in human chondrocytes and fibroblast‐like synovial cells . Glycated HSA and/or glycated bovine serum albumin (BSA) also stimulated IL‐6 and IL‐8 produced by gingival fibroblasts and monocyte/macrophages .…”
Section: Discussionsupporting
confidence: 93%
“…Endotoxin levels in G‐HSA and HSA were measured at 13 ± 0.5 and 8.3 ± 1 pg/mL, respectively (Table ). In our previous studies and others, 1 μg/mL Escherichia coli or P. gingivalis LPS (10 6 ‐fold greater than levels detected in these preparations) was needed to stimulate IL‐6 production by human gingival fibroblasts.…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations